ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA MANAJERIAL DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Anita Dyah Pamulatsih, Bambang Widarno & Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study is 1) to analyze the significance of the effect of accounting implementation on accountability of managerial performance, 2) to analyze the significance of the effect of accounting accountability application on employee work motivation 3) to analyze the significance of the effect of work motivation on managerial performance and 4) to analyze the effect of the application of accounting accountability to managerial performance with work motivation as intervening variable. The scope of the study is a survey of KJKS Bina Insan Mandiri Karanganyar employees. The population of 31 employees and the whole is used as a sample. Methods of data collection used questionnaires and literature study. Data analysis technique used path analysis. The results showed that the application of responsibility accounting and work motivation has a positive and significant effect on managerial performance. Implementation of accountancy accountability positive but not significant effect on employee motivation Work motivation does not mediate the effect of accounting implementation of accountability to managerial performance.Keywords: accountancy accountability, work motivation, managerial performance